Making artworks valuable: Categorisation and modes of valuation work - Plante, Maude; Free, Clinton; Andon, Paul (Accounting, Organizations and Society, 2021)
Art represents one of the world’s most sacred cultural resources, with the total value of artworks currently in circulation worldwide estimated to exceed $1.5 trillion. Despite its undoubted historical and cultural significance, art, like other culture-based assets, has been frequently qualified as ‘difficult to value’. This study aims to understand the ways in which valuation work constructs artworks as being of value. Building upon research into categorisation and valuation work, we present our findings based on 41 interviews with agents specialised in art valuation (art dealers, art auctioneers, and art valuers) in the United States and Australia, combined with one year of participant observation at a major international art institution. We distinguish four categories of artworks according to their degree of cultural recognition: decorative art, emerging art, trending art, and blue-chip art. Depending on how an art production is categorised, we find that actors engage in three different modes of overlapping and mutually constitutive valuation work: interpreting, credentialing, and projecting value. This categorisation of cultural significance makes the valuation of artworks both hierarchical and performative.